(untitled) (Journal of Tropical Pharmacy and Chemistry, 2013)
The ethanolic extract from the bulb of Eleutherine americana was investigated for acute and subacute toxicity in Balb/C male mice. The parameter used on this research is mortality n hepar histophatological. During acute toxicity study, bulb plant (0.52, 0,26 and 5.2 mg/kg b.wt) p.o. for 72 hour and subacute toxicity study bulb plant (0.52, 0,26 and 5.2 mg/kg b.wt) p.o. once daily for 30 days. The result of the research shows that ethanol extract with 0.52, 0,26 and 5.2 mg/kg b.wt dosage can be said relatively safe because there is no death signal about 50% in 24 hour and the result of subacute toxicity in observation histophatological in hepar shows there is fibrosis n necrosis with 0.52, 2.6 mg/kg b.wt and 5.2 mg/kg b.wt dosage.